1981
DOI: 10.1093/brain/104.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Gating of Somatosensory Evoked Potentials During Different Kinds of Movement in Man

Abstract: 1. Somatosensory evoked potentials from electrical stimulation of the digital nerves of the right thumb have been recorded during the performance of various motor tasks in eight normal subjects. 2. The N20-P30 primary cortical response is only moderately affected by task context, while the P45-N55 secondary response is markedly 'gated' by movement of the stimulated digit. The late N140 vertex is variable. 3. In most subjects, active and passive movements are about equally effective in suppressing the secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
136
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(161 citation statements)
references
References 0 publications
16
136
1
Order By: Relevance
“…Transient reductions in SEPs have been reported previously in conjunction with finger and limb movement (Papakostopoulos et al 1975;Rushton et al 1981;Starr and Cohen 1985). The reduction has been attributed to the idea that the nervous system suppresses sensory inflow associated with self-initiated movement.…”
Section: Discussionmentioning
confidence: 77%
“…Transient reductions in SEPs have been reported previously in conjunction with finger and limb movement (Papakostopoulos et al 1975;Rushton et al 1981;Starr and Cohen 1985). The reduction has been attributed to the idea that the nervous system suppresses sensory inflow associated with self-initiated movement.…”
Section: Discussionmentioning
confidence: 77%
“…It has been reported that cortical somatosensory evoked potentials are decreased in amplitude during movement (Giblin 1964;Coquery and Vitton 1972;Hazemann et al 1975;Papakostopoulos et al 1975;Rushton et al 1981;Chapman et al 1984;Start and Cohen 1985). One might speculate that if subjective intensity is determined on the basis of the central neural code then, when neural discharge is diminished, there would be a parallel decrease in the subjective intensity of the stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The amplitude of evoked potentials in the lemniscal system decreases prior to and during voluntary limb movements in cats (Ghez and Lenzi 1971;Ghez and Pisa 1972;Coulter 1974), monkeys (Dyhre-Poulson 1978;Chapman et al 1984) and man Offprint requests to: C.E. Chapman, Centre de Recherche en Sciences Neurologiques, Universit6 de Montr6al, PO Box 6128, Station A, Montrral, Qu6bec, H3C 3J7, Canada (Giblin 1964;Coquery and Vitton 1972;Lee and White 1974;Hazemann et al 1975;Papakostopoulos et al 1975;Rushton et al 1981;Starr and Cohen 1985). In keeping with these findings, psychophysical experiments have shown that the threshold for detecting cutaneous stimuli rises when the stimulated area is actively moved (Coquery et al 1971;Garland and Angel 1974;Dyhre-Poulson 1978;Angel and Malenka 1982) and this change can precede the onset of movement (Coquery 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Modification of central sensory processes dunng motor activity l~ referred to as 'gating' and has been described for somatosensory (Papakostopoulos et al 1975, Rushton et al 1981, an&tory (Start 1964, Hazemann et al 1975 and visual inputs (Volkmann 1962, Adey andNoda 1973) In the somatosensory system 'gating' begins even before movement onset, during the precontractlon penod (Coulter 1974, Starr andCohen 1985) lmphcatmg the action of central efferent systems m the modulation of sensory reformation Asanuma (1981) suggested that activity of the pyramidal tract may influence the transmission of afferent impulses to higher centers including the motor cortex However, details as to the relationship between the types of movement and the selectivity of afferent input modification are not known This report utilizes scalp recordings of somatosensory evoked potentials m humans to demonstrate that somatosensory evoked potentials derived from stimulating a particular peripheral nerve are modified specifically for movements Involving the body parts Innervated by that particular nerve…”
mentioning
confidence: 99%